2020
DOI: 10.1007/s12289-020-01559-8
|View full text |Cite
|
Sign up to set email alerts
|

Thermo-mechanical characterization of unsaturated polyester/glass fiber composites for recycling

Abstract: Unsaturated-polyester/glass-fiber composites are worldwide more and more used. Actually, their thermochemical and mechanical recycling paths are quite well-known. But, due to the relatively low value of the end products, these two paths are hardly economically viable. Thus, a third way will be proposed as a thermomechanical path. In order to recycle these composites, a study of their thermo-mechanical behaviors is proposed in this work, through various static and dynamic tests at temperatures ranging from ambi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…Prolonging the reaction time at a specific temperature may negatively affect the molecular weight as it can lead to secondary reactions that reduce the weight. In industrial syntheses, it is often preferred to extend the reaction time rather than using a catalyst that could compromise the quality of the polyester [30][31][32][33]. Based on experimental data, it has been found that the reverse reactions in the esterification process can be ignored at temperatures below 180 • C and/or conversions lower than 95%.…”
Section: Resultsmentioning
confidence: 99%
“…Prolonging the reaction time at a specific temperature may negatively affect the molecular weight as it can lead to secondary reactions that reduce the weight. In industrial syntheses, it is often preferred to extend the reaction time rather than using a catalyst that could compromise the quality of the polyester [30][31][32][33]. Based on experimental data, it has been found that the reverse reactions in the esterification process can be ignored at temperatures below 180 • C and/or conversions lower than 95%.…”
Section: Resultsmentioning
confidence: 99%
“…The wide use of these polymers in tanks, tubes, vessels, outdoor applications and many other aggressive environments, makes it necessary to well understand their long-term stability in the presence of external factors that cause physical and mechanical degradation, such as temperature, oxygen, water, chemicals, radiations, etc [9,10]. In recent years, a large number of studies related to the physicalmechanical properties of epoxy and polyester matrix composites after ageing in different environments have been carried out [11][12][13][14][15][16][17]. However, the study of these neat polymers, which can have many other applications in addition to composite matrices, and the comparison of their properties after the ageing process through robust statistical analysis, is still very limited.…”
Section: Introductionmentioning
confidence: 99%